ANALISIS KLASIFIKASI BARANG EKSPOR PRODUK SAMPINGAN DAN LIMBAH PABRIK MINYAK SAWIT - Muh.Sutartib; Purwana, Aditya Subur (Unit Penerbitan Politeknik Keuangan Negara STAN, 2025)
Palm oil processing factories that produce Crude Palm Oil (CPO) and its derivatives also generate by-products. Although these by-products are categorized as waste, they still possess potential nutritional value and added economic value that can be optimized. One notable by-product is liquid waste known as Palm Oil Mill Effluent (POME). CPO and several of its derivatives are export commodities subject to Export Duty (Bea Keluar/BK) and/or levies imposed by the Public Service Agency of the Palm Oil Plantation Fund Management Agency (BPDPKS), referred to as Export Levy (Pungutan Ekspor/PE). The classification of CPO by-products may lead to disagreements between the Directorate General of Customs and Excise (DGCE) and exporters, which can escalate into formal objections to DGCE decisions or appeals to the Tax Court. This research aims to analyze the product classification of CPO-derived by-products that have undergone specific treatments and to evaluate the BK and PE tariffs applied to both on-grade and off-grade CPO. A qualitative research method is employed, supported by secondary quantitative data from 2021 to 2024, including BK and PE tariff data, as well as records of objections and appeals. Qualitative data are gathered from literature reviews and case studies of CPO exports. The analysis reveals that the Harmonized System (HS) classification stated in regulations issued by the Ministry of Industry, BPDPKS levy provisions, and BK regulations do not fully comply with HS classification principles. In some cases, the classification of CPO by-products in BPDPKS regulations is inconsistent with those in BK regulations. Moreover, the current ad valorem PE tariffs fail to ensure fairness, as both high-quality and low-quality CPO are subject to the same levy despite considerable differences in international market prices.